Out of pocket expenditure among Rashtriya Swasthya Bima Yojana beneficiary and non-beneficiary patients admitted to a tertiary care centre, Berhampur, India: a comparative study - Satapathy, Sushree Priyadarsini; Karmee, Nivedita; Satapathy, Durga Madhab; Tripathy, Radha Madhab (International Journal of Advances in Medicine, 2019)
Background: RSBY, a health insurance scheme, was launched by the Indian government to protect BPL families from incurring financial liabilities which are likely to occur due to hospitalization. Objectives was to compare over all OOPE among RSBY beneficiaries and non-beneficiaries and to estimate its extent during hospitalization in different domains among RSBY beneficiaries and non-beneficiaries. Methods: It was a cross-sectional study conducted for 2 months (January-February 2018) among BPL families residing in Ganjam district, Odisha. Multistage random sampling was done. Total sample size was 256, the number of beneficiaries and non beneficiaries taken was 128 each. Results: Non beneficiaries incurred higher overall OOPE higher i.e. 95.3% than the Beneficiaries and it was found to be statistically significant with x²=74.8 and P-value <0.001. Among beneficiaries out of pocket expenditure was found in 46.1% of the study population. 45.3% of beneficiaries had to borrow partially from friends and relatives to fulfil their hospital related expenses followed by 32% borrowing fully for their treatment. Among beneficiaries, most out of pocket expenditure was for life support services as they sought treatment mostly for surgical conditions. Conclusions: Health insurance coverage should be improved by increasing enrolment. People should be made aware about the services covered under the schemes.